Impact of the COVID-19 pandemic on employment: Findings from national labour surveys in five Latin American countries - Martha Alter Chen; Joann Vanek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper provides a comparative summary of recent national statistics from five Latin American countries on employment losses and gains during the peak COVID-19 years compared with pre-pandemic levels. As part of its work on the impact of the pandemic on informal workers, the Women in Informal Employment: Globalizing and Organizing (WIEGO) network commissioned analyses of recent national labour force data in Brazil, Chile, El Salvador, Mexico, and Peru; and undertook a separate analysis of South African data on employment losses and gains during COVID-19 (see Rogan and Skinner 2022). This paper also presents, in Section 2, micro-evidence from a WIEGO-led study of the impact of COVID-19 on informal workers. This information supplements the national statistics in Section 1, with information on the dynamics of employment losses and gains for workers in specific groups of urban informal workers. It is based on a panel study carried out by the WIEGO network in mid-2020 and mid-2021 on the impact of the pandemic on informal workers in 11 cities around the world, using both a survey questionnaire and in-depth interviews (see Chen et al. 2022a). The paper concludes with reflections on the use of mixed data sources and research methods and on policy responses to the informal economy going forward.
Keywords: 330; formal employment; informal employment; employment losses; COVID-19 pandemic